2022
DOI: 10.3390/su14042309
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Diet Optimization Targeting Dietary Water Footprint Reduction—A Country-Specific Study

Abstract: Food production creates 70% of the total anthropogenic water footprint, and it is the main cause of water pollution. Thus, more sustainable diets could contribute to the achievement of the Sustainable Development Goals. A linear programming-based stepwise optimization was designed to create dietary water footprint-reduced, culturally acceptable, and healthier diets in the case of Hungary based on a representative dietary survey. Optimization resulted in a considerable total dietary water footprint reduction (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In the vegan scenario in this study, 532 g of soy drink was suggested by the model, while in the current diet only 9 g was consumed, questioning acceptability of the calculated diet. To account for acceptability, food item-based models need constraints based on expert opinion to preserve implicit associations and interdependent quantities of food items [ 11 , 19 , 49 ]. Furthermore, in food item-based models, uncertainties in the data can have a large influence on the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vegan scenario in this study, 532 g of soy drink was suggested by the model, while in the current diet only 9 g was consumed, questioning acceptability of the calculated diet. To account for acceptability, food item-based models need constraints based on expert opinion to preserve implicit associations and interdependent quantities of food items [ 11 , 19 , 49 ]. Furthermore, in food item-based models, uncertainties in the data can have a large influence on the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in food item-based models, uncertainties in the data can have a large influence on the outcome. Therefore, several studies based their optimization on linear combinations of food groups instead of food items [ 49 , 50 ]. However, food grouping reduces the detail of the data and remains an arbitrary process.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a diet modeling study that aimed at minimizing WU (in the first step of a hierarchical optimization approach) in food systems was conducted using Hungarian data (32). This study documented a maximum reduction in diet-related water footprint of 19.5% for women and 28.2% for men, these effect sizes being much lower than those we found herein.…”
Section: Discussionmentioning
confidence: 99%
“…A nation is considered to be developed if its citizens are rich and its environment is sustainable. In this nation, there are, nonetheless, areas with excellent economic indicators but low Environmental Quality [22]. People often relocate to find work and earn greater pay, for instance in the capital city where most people believe the minimum salary to be high.…”
Section: The Effect Of the Environmental Quality Index On Sustainable...mentioning
confidence: 99%
“…Meanwhile, according to Kartiasih and Pribadi [21] the Environmental Quality Index is a score that can be interpreted into numerous areas and indicates how effectively a country is at implementing environmental laws or the success of environmental policies. According to Tompa et al [22] the Environmental Quality Index indicators comprise 3 (three) indicators: water quality index, air quality index, and land cover quality index. Environmental Quality Index values can be classified into the following ranges (see Table 1).…”
Section: Introductionmentioning
confidence: 99%